Australia : 2012 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Australia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2012)
GDP growth is likely to remain strong, although narrowly driven by a mining investment boom, increasing the economy's vulnerability to terms of trade shocks. Outside the mining sector, growth is expected to be slow with still weak consumer confidence and a strong exchange rate weighing on business investment. The main risks are external, and include an intensification of the euro crisis and a sharper-than-expected slowdown in China.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet